2013
DOI: 10.2214/ajr.12.9672
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Breast Tomosynthesis in a Routine Screening Practice: An Observational Study

Abstract: The introduction of breast tomosynthesis into our practice was associated with a significant reduction in recall rates and a simultaneous increase in breast cancer detection rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
158
3
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 307 publications
(183 citation statements)
references
References 25 publications
15
158
3
4
Order By: Relevance
“…The improvement in specificity for 2D + DBT compared with 2D alone was observed irrespective of mammographic density, age, tumour size and dominant radiological feature and in both invasive cancers and DCIS, as noted previously, 16,59,60 and indicates the potential of integrated DBT to improve specificity by allowing readers to avoid recalling false negative cases. In agreement with published studies, 17,45,141 ROC analysis demonstrated a significant increase in diagnostic accuracy for 2D + DBT compared with 2D alone and was most likely attributable to the marked improvement in specificity.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…The improvement in specificity for 2D + DBT compared with 2D alone was observed irrespective of mammographic density, age, tumour size and dominant radiological feature and in both invasive cancers and DCIS, as noted previously, 16,59,60 and indicates the potential of integrated DBT to improve specificity by allowing readers to avoid recalling false negative cases. In agreement with published studies, 17,45,141 ROC analysis demonstrated a significant increase in diagnostic accuracy for 2D + DBT compared with 2D alone and was most likely attributable to the marked improvement in specificity.…”
Section: Resultssupporting
confidence: 76%
“…Non-significant increases in cancer detection ranging from 4.3% to 49.0% have been reported in several screening studies after the addition of DBT; 59,60,138,139 in these cases lack of statistical significance was largely attributable to sample size limitations. Our results differ from data from two prospective screening trials comparing 2D + DBT and 2D alone.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations